JUDICIAL DISCRETION IN THE CRIMINAL JUSTICE PROCESS IN INDONESIA (A Study at the Cianjur District Court) - Anissa Larasati; Faizin Sulistio; I Nyoman Nurjaya (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The influence of public attention on the criminal trial process is currently affecting the judiciary under the Supreme Court of the Republic of Indonesia, where all layers of society consistently follow the development of news related to ongoing trials in specific legal jurisdictions. This article focuses on discussing the nature of public attention, emphasizing that it should not affect the judges' rulings in criminal cases, as well as the discretion of judges in formulating legal considerations in cases that attract public attention during the decision-making process. Our findings indicate that in making legal considerations for criminal case rulings, the panel of judges must always adhere to the formal procedural law established in the criminal trial process, reinforced by the application of the Indonesian Criminal Procedure Code, relevant criminal laws in the trial, and the Supreme Court regulations. The primary guidance for judges in formulating legal considerations for legal decisions must be based on at least two pieces of evidence proven during the trial, coupled with the conviction of the presiding judge, and supplemented by the judge's authority to exercise discretion in order to ensure clear and just resolution of the criminal case. In conclusion, we recommend that judges must continue to uphold their independence in making legal considerations and delivering sound legal judgments.